Kepemimpinan Kepala Sekolah dalam Era Otonomi Pendidikan - Baharuddin, Baharuddin (el Harakah: Jurnal Budaya Islam, 2006)
The leadership of headmaster has active aims in increasing the education quality, so that good leadership capability is required.  Good leadership can arrange all of education resources for getting education purpose either the learning aspect or developing human resources. Accordingly the headmaster is demanded to be able to create good organization climate as well. It is in order that all of the school components can take a part to gain the objectives and aims of school organization. This paper reviews several leadership theories that are applicable in education context. It covers great man theory, contingency theory, transformational theory and leadership through emotional intelligence approach. Furthermore, it also discusses the characteristics of headmaster who is visionary and transformative. Headmaster also takes role as the model of initiation, inspiration, participation and motivation for all of the school components. Kepemimpinan kepala sekolah memiliki tujuan aktif dalam meningkatkan kualitas pendidikan, sehingga diperlukan kemampuan kepemimpinan yang baik. Kepemimpinan yang baik dapat mengatur semua sumber pendidikan untuk mendapatkan tujuan pendidikan baik aspek pembelajaran maupun pengembangan sumber daya manusia. Dengan demikian kepala sekolah dituntut untuk dapat menciptakan iklim organisasi yang baik pula. Hal ini agar semua komponen sekolah dapat mengambil bagian untuk mendapatkan tujuan dan tujuan organisasi sekolah. Makalah ini mengulas beberapa teori kepemimpinan yang berlaku dalam konteks pendidikan. Ini mencakup teori orang hebat, teori kontingensi, teori transformasional dan kepemimpinan melalui pendekatan kecerdasan emosional. Selanjutnya, ia juga membahas karakteristik kepala sekolah yang visioner dan transformatif. Kepala sekolah juga berperan sebagai model inisiasi, inspirasi, partisipasi dan motivasi untuk semua komponen sekolah.